Modeling the Physisorption of Bisphenol a on Graphene and Graphene Oxide - Cortes-Arriagada, D; Santander-Nelli, M; Santander-Nelli, M (2013)
The physisorption of bisphenol A (BPA) on pristine and oxidized graphene was studied theoretically via calculations performed at the PBE-D3 level (including dispersion force corrections). Three stable conformations of BPA on graphene were found. A lying-down configuration was energetically favored because the presence of ?-? stacking and dispersion forces increased interactions. In addition, the adsorption of BPA on the edges of graphene oxide was enhanced when adsorption occurred on carboxyl and carbonyl groups, whereas the adsorption strength decreased when adsorption occurred on hydroxyl groups. The highest physisorption strength was obtained on the surface of graphene oxide due to the presence of ?-? stacking and dispersion forces (which provided the greatest contribution to the adsorption energy) as well as hydrogen bonds (which provided a smaller contribution), indicating that oxidized graphene is a better candidate than pristine graphene for BPA removal. On the other hand, an increase in electrophilicity was observed after the physisorption of BPA in all systems (with respect to graphene and BPA in their isolated forms), with the adsorbent acting as the electron acceptor. Finally, molecular dynamics simulations performed using the PM6 Hamiltonian showed that the adsorption of BPA on graphene is stable. © 2013 Springer-Verlag Berlin Heidelberg.